MAHKAMAH KONSTITUSI DALAM MENEGAKKAN KEADILAN KONSTITUSIONAL DI ERA MODERN - Ilham, Muhammad (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to examine the role of the Constitutional Court (MK) in upholding constitutional justice in Indonesia in the modern era using a substantive justice approach. The research method used is normative juridical. The data used is secondary data, obtained from library materials through literature and documentation studies, then analyzed qualitatively. Descriptive data analysis techniques. The results showed that in the concept of